The Effect of START Triage Simulation Method on the Preparedness of Puskesmas Nurses at Risk Disaster in Helping Victims in Ternate - Muhammad, Aminudin; Ahmad, Safrudin L (Jurnal Kesehatan, 2023)
Background: Disasters can cause deaths, injuries, damage to health facilities and public health problems. An effective approach is needed in handling victims through triage. Objective; analyzed the effect of the START triage method simulation on preparedness to help disaster victims by nurses at the Disaster Prone Health Center in Ternate City. Method: This research design is quasi experimental Pretest-posttest Control Group Design. The sample for this research is 50 nursing staff spread across 4 health centers in disaster-prone areas. The instruments used were questionnaires and observation sheets. Data analysis used the Wilcoxon test. Results: The research results showed that using the Wilcoxon test (Î±=0.05), the p value for the control group was 0.001 and the p value for the treatment group was 0.000. Conclusion: Providing the START triage method simulation to the treatment group had an effect on preparedness to help disaster victims by community health center nurses.